Cycles of Debt and Punishment: A Symposium on Prisons of Debt: The Afterlives of Incarcerated Fathers - Williams, Jason M. (The prison journal, 2023)
In the contemporary United States, millions of fathers cycle through the criminal justice and child support systems—cycles that create new forms of debt and disadvantage. This symposium discusses those cycles and their effects on fathers and their families. Through comments on Lynne Haney's book, Prisons of Debt: The Afterlives of Incarcerated Fathers, the authors analyze the criminalization of child support and the ways it complicates reentry after prison. They engage Haney's arguments about the causes and consequences of prisons of debt and her empirical material on men's struggles as indebted fathers—or, as Michael Mitchell put it, the book's insistence on “getting proximate to human suffering.”